Experimental Study on the Effect of Flow Velocity and Slope on Stream Bank Stability (Part II) - Kadhim, Jawad; Waheed, Mohanned Q.; Hussein, Haitham A.; Al-Wakel, Saad F. A. (Civil Engineering Journal, 2024)
Erosion significantly contributes to the instability of riverbanks. The current study considers the issues of instability and erosion that plague the banks of the Al-Muwahada channel. It was a large irrigation channel located west of Baghdad, Iraq. A laboratory flume was constructed to gain a comprehensive understanding of the erosion process on riverbanks. This flume serves as a scaled-down replica of the Almowahada channel. The main structure of the flume consists of a 3-meter steel construction with dimensions of 1 meter in width and 0.6 meters in height. In order to reduce the high flow velocity, it was periodically linked to quieting tanks with dimensions of 1 meter in width, 1.5 meters in height, and 0.4 meters in thickness. The flume's sidewalls are constructed with plexiglass that is 4 mm in thickness. Furthermore, a water reservoir with a capacity of 1800 liters was introduced into the flume. A riverbank was constructed with two slope angles, one at 45º and the other at 60º. The bank was then subjected to five different velocities. The experimental results indicate the velocity of flow and slope angle of the riverbank are the primary factors that influence the stability of the riverbank. The tipping point between erosion and deposition rises increasingly as the flow velocity increases. The majority of the sediment at the bottom, particularly on the near side of the bank, is the result of bank erosion. As the slope angle of the riverbank approaches 37°, it becomes more stable. The erosion-induced deformation in the riverbank with a slope angle of 45º is greater than that in the riverbank with a slope angle of 60º. The investigation demonstrated that the 45° angle is more susceptible to erosion caused by the flow velocity than the 60° angle. Doi: 10.28991/CEJ-2024-010-10-012 Full Text: PDF